Analisis Komprehensif Pendekatan Pedagogis dalam Pendidikan Gerak dan Olahraga - Harahap, Ganda Marito; Kurniati, Uci; Harahap, Aprina; Yunus, Fadhilah; Suyono, Suyono (LPPPI Publishing, 2025)
Movement and sports education plays an important role in the formation of students' motor skills, health and character. However, challenges in implementing pedagogical approaches often become obstacles in achieving learning goals. This article examines pedagogical approaches in movement and sport education through a literature study, with a focus on pedagogical theory, learning strategies, and implementation challenges. The research problem raised is the lack of a comprehensive understanding of relevant pedagogical approaches in movement education. This research aims to provide an in-depth overview of effective and applicable pedagogical approaches. The method used is a literature study, with analysis of various scientific sources and policy documents. The results of the study show that approaches based on constructivism, competence and humanism have high relevance in movement education. Effective implementation requires structured learning planning, process-oriented evaluation, and adaptation to modern technology. The main challenges include limited facilities and infrastructure and low teacher competency. This article suggests that future research should focus more on empirical evaluation of the effectiveness of specific pedagogical approaches in the context of movement education. In addition, teacher training and professional development also needs to be improved to support the implementation of innovative approaches.